2009
DOI: 10.2337/db08-0981
|View full text |Cite
|
Sign up to set email alerts
|

m.3243A>G Mutation in Mitochondrial DNA Leads to Decreased Insulin Sensitivity in Skeletal Muscle and to Progressive β-Cell Dysfunction

Abstract: OBJECTIVE-To study insulin sensitivity and perfusion in skeletal muscle together with the ␤-cell function in subjects with the m.3243AϾG mutation in mitochondrial DNA, the most common cause of mitochondrial diabetes. These patients included five subjects with no diabetes as defined by the oral glucose tolerance test (OGTT) (group 1), three with GHb Ͻ6.1% and newly found diabetes by OGTT (group 2), and seven with a previously diagnosed diabetes (group 3). Control subjects consisted of 13 healthy individuals who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 50 publications
(58 reference statements)
3
29
1
Order By: Relevance
“…There are two possible reasons why this case showed insulin resistance. One is a low serum adiponectin level that might have been derived from a fat tissue dysfunction (13), while the other is the loss of skeletal muscle mass associated with the mitochondrial mutation (9,11,14). Other factors such as ectopic fat (23) and inflammation (24) are also thought to be associated with insulin resistance, but we could not find any ectopic fat deposition or increases of inflammatory markers such as IL-6 and TNF-alpha in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible reasons why this case showed insulin resistance. One is a low serum adiponectin level that might have been derived from a fat tissue dysfunction (13), while the other is the loss of skeletal muscle mass associated with the mitochondrial mutation (9,11,14). Other factors such as ectopic fat (23) and inflammation (24) are also thought to be associated with insulin resistance, but we could not find any ectopic fat deposition or increases of inflammatory markers such as IL-6 and TNF-alpha in this case.…”
Section: Discussionmentioning
confidence: 99%
“…The 3243 A>G mutation in mtDNA reduces the level of ATP generation because of the disruption of the electron transport system (ETS), and the altered ATP to ADP ratio may result in impaired insulin secretion, which can lead to beta-cell apoptosis (6)(7)(8). A decreased insulin sensitivity is also observed in mitochondrial diabetes (9,10). The generation of reactive oxygen species (ROS) in mitochondria due to the disruption of oxidative phosphorylation may cause skeletal muscle atrophy (9-11) and adipose tissue dysfunction, such as the dysregulation of adipocytokines (12, 13), which might lead to an impaired glucose uptake (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…the target for astrocytic nitric oxide [23] has also been shown [24,25]. Importantly, a study comparing glucose and oxygen metabolism in patients carrying mitochondrial DNA mutations, to PD patients, concluded that impaired mitochondrial functioning is not a primary insult in the pathogenesis of PD and that damage to the mitochondria may occur instead as a result of intracellular changes taking place [26].…”
Section: -Methyl-4-phenylpyridinium Ion (Mpp+)mentioning
confidence: 99%
“…At 0 min, a standard primed hyperinsulinemiceuglycemic clamp was started and was continued for 220 min using 1 mU·kg -1 ·min -1 intravenous insulin infusion as previously described (Lindroos et al 2009 10 (4-105)** c * 1 Hb-A1 C (%) 5.3 (4.9-6.1) 6.0 (5.0-9.9) 0.003 5.2 (5.0-6.0) 6.0 (5.8-6.1) 7.5 (5.9-9.9)** al FFAs (mmol/l) 0.42 (0.20-0.91) 0.55 (0.24-1.12) 0.15 0.40 (0.25-0.81) 0.46 (0.39-1.12) 0.67 (0.24-1.11)…”
Section: Designmentioning
confidence: 99%
“…In the study presented here, insulin-stimulated glucose uptake in the liver and in subcutaneous fat was quantified using positron emission tomography (PET) in patients with the m.3243A>G mutation,who had been previously characterized for their beta cell function and skeletal muscle insulin sensitivity (Lindroos et al 2009). In addition, liver fat content was measured with proton magnetic resonance spectroscopy ( 1 H MRS).…”
Section: Introductionmentioning
confidence: 99%